If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(8 + 2x) = (3x + 12) (8 * x + 2x * x) = (3x + 12) (8x + 2x2) = (3x + 12) Reorder the terms: 8x + 2x2 = (12 + 3x) Remove parenthesis around (12 + 3x) 8x + 2x2 = 12 + 3x Solving 8x + 2x2 = 12 + 3x Solving for variable 'x'. Reorder the terms: -12 + 8x + -3x + 2x2 = 12 + 3x + -12 + -3x Combine like terms: 8x + -3x = 5x -12 + 5x + 2x2 = 12 + 3x + -12 + -3x Reorder the terms: -12 + 5x + 2x2 = 12 + -12 + 3x + -3x Combine like terms: 12 + -12 = 0 -12 + 5x + 2x2 = 0 + 3x + -3x -12 + 5x + 2x2 = 3x + -3x Combine like terms: 3x + -3x = 0 -12 + 5x + 2x2 = 0 Factor a trinomial. (-4 + -1x)(3 + -2x) = 0Subproblem 1
Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4Subproblem 2
Set the factor '(3 + -2x)' equal to zero and attempt to solve: Simplifying 3 + -2x = 0 Solving 3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = 0 + -3 -2x = 0 + -3 Combine like terms: 0 + -3 = -3 -2x = -3 Divide each side by '-2'. x = 1.5 Simplifying x = 1.5Solution
x = {-4, 1.5}
| 19000-200x-200*(x-5)=0 | | 3m/5*20 | | 36x^2+12xy-24y^2= | | 3m/5x20 | | 4000/6000 | | 20x^2+61x+35=0 | | 5-4x=9+7x | | 6x^4-9x^2=8 | | 0.5(6c+4)-2(c+1.5)=0.6(9-3c) | | (5-u)(5u+6)=0 | | 5x^2+11y-36=0 | | Qx=5+2P | | 12+7-5+100-9= | | 3x-2=8x+4 | | 0.5(12-4s^2)-2s(1-s)=8 | | -(3/5)*(-4) | | z^2-16z+64=0 | | 0.8x+7.7x=-1 | | 9x+9=-189 | | 3x+13=117 | | 5x-40+3x+10=180 | | (5/6y)-(1/6)=7/3 | | 5x+35y=30 | | f(x)=6/5x | | .4(6/20) | | x^3-25x=x-100 | | 0.2(6t+0.7)=9.74 | | 48+112x-16x^2=0 | | f(9.0)=2.8x+7.9 | | 4t(11t+7)=0 | | x+40=3+x | | 8-a/b/16/b |